Synchronous Ganglioneuroma and Schwannoma Mistaken for Carotid Body Tumor - Konstantinos Paraskevopoulos; Angeliki Cheva; Styliani Papaemmanuil; Konstantinos Vahtsevanos; Konstantinos Antoniades (Case Reports in Otolaryngology)
Ganglioneuromas are a very rare benign neural tumor, commonly derived from the ganglia of the sympathetic system, and are composed of mature Schwann cells, ganglion cells, and nerve fibres. They may arise anywhere from the base of the skull to the pelvis along the paravertebral sympathetic plexus. We report a rare case of synchronous ganglioneuroma and schwannoma, mistaken for carotid body tumor. The coexistence of these two entities in head and neck region is very rare.